2017
DOI: 10.3892/etm.2017.5363
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of diffusion tensor imaging parameters and Gleason scores of prostate cancer

Abstract: Abstract. The aim of the present study was to explore the association between the parameters of diffusion tensor imaging (DTI), including fractional anisotropy (FA) values, apparent diffusion coefficient (ADC) values and the diffusion tensor tractography (DTT) map, with the Gleason score of prostate cancer (PCa). A retrospective study of 50 cases of PCa confirmed by biopsy or surgical pathology was performed. Conventional magnetic resonance imaging and DTI scans were conducted in these cases. The 50 cases of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
3
2
0
Order By: Relevance
“…Furthermore, we found that MD showed negative correlation with Glasson score with statistically significant results (p value = 0.013). These alterations may be because of the progressively dense arrangement of cells in the tumors of high grades; additionally, the extracellular space decreases [17]. This coincides with Tian W, et al [17] who found nearly the same results.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Furthermore, we found that MD showed negative correlation with Glasson score with statistically significant results (p value = 0.013). These alterations may be because of the progressively dense arrangement of cells in the tumors of high grades; additionally, the extracellular space decreases [17]. This coincides with Tian W, et al [17] who found nearly the same results.…”
Section: Discussionsupporting
confidence: 79%
“…These alterations may be because of the progressively dense arrangement of cells in the tumors of high grades; additionally, the extracellular space decreases [17]. This coincides with Tian W, et al [17] who found nearly the same results. This is not consistent with Wang S, et al who reported a negative correlation between the values of FA and Gleason scores, signifying that an elevation in Gleason scores will lead to a slowly decrease in the value of FA [25].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The traditional magnetic resonance imaging (MRI) scan can reveal the intracranial structure, intracranial tumor size, location and surrounding edema; however, it cannot precisely reveal the shape of the intracranial nerve fibers. With the development of high-field MR and computer technology, diffusion tensor imaging (DTI) has enabled non-invasive studies of the white matter fiber fascicle (1). DT tractography (DTT), which is developed from DTI, can reflect the pathological state of the white matter fiber fascicle and the anatomical connection with adjacent lesions, and assist the surgeon to design a suitable surgical strategy prior to surgery (2).…”
Section: Introductionmentioning
confidence: 99%
“…Because water diffusion in biological tissue is often anisotropic, and not isotropic, i.e., equal in all directions, the concept of a diffusion tensor captures and quantifies this (fractional) anisotropy, thus enabling investigation of preferred tracts of diffusion, e.g., along neuronal fibers in brain tissue or peripheral nerves 66 , 67 . Although used primarily in neuro-oncology 68 , this method has also been shown to be beneficial in determining the histological grade of oral carcinoma 69 ; discriminating between small-cell lung cancer and non-small cell lung cancer brain metastases 70 ; correlating with Gleason scores in prostate cancer 71 ; or predicting parametrial infiltration in cervical cancer 72 .…”
Section: Mrimentioning
confidence: 99%